An MCNP study of fast neutron interrogation for standoff detection of improvised explosive devices - Heider, Samuel A. (Kansas State University, 2012)
The signature-based radiation-scanning (SBRS) technique relies on radiation detector responses, called “signatures,” and compares them to “templates”, to differentiate targets containing nitrogen-rich explosives from those that do not. This investigation utilizes nine signatures due to inelastic-scatter and prompt-capture gamma rays from hydrogen, carbon, nitrogen, and oxygen (HCNO) as well as two neutron signatures, produced when a target is interrogated with a 14.1 MeV neutron source beam. One hundred and forty three simulated experiments were conducted using MCNP5. Signatures of 42 targets containing explosive samples (21 of RDX and 21 of Urea Nitrate), and 21 containing inert samples were compared with the signatures of 80 artificial templates through figure-of-merit analysis. A density filter, comparing targets with templates of similar average density was investigated. Both high and low-density explosives (RDX-1.8 g cm-3 and Urea Nitrate-0.69 g cm-3) were shown to be differentiated from inert materials through use of neutron and gamma-ray signature templates with sensitivity of 90.5% and specificity of 76.2%. Density Groups were identified, in which neutron signature templates, gamma-ray signature templates or the combination of neutron and gamma-ray signature templates were capable of improving inert-explosive differentiation. figure-of -merit analysis, employing the best Density Group specific templates, differentiated explosive from inert targets with 90.5% sensitivity and specificity of over 85%.
Keywords: Monte Carlo; Signature based radiation scanning; Improvised explosive devices; Explosive detection; Nuclear Engineering (0552)